Optimization of the enzymatic hydrolysis process for sea buckthorn leaf polysaccharides: an investigation into their enhanced physicochemical properties and antioxidant activities - Yuning An; Buyu Wang; Ziqi Meng; Yifeng Song; Yuan Wang; Wenwen Wang; Ming Xu; Xiaoping An (Chemical and Biological Technologies in Agriculture)
Abstract Sea buckthorn leaves (Hippophae rhamnoides L.) (SBL) are considered a promising new source of antioxidants. The process of enzymatic hydrolysis facilitates the breakdown of plant cell walls, promoting the release of polysaccharides. In this study, we optimized the enzymatic hydrolysis process of SBL to enhance the release of polysaccharides, resulting in enzymatically hydrolyzed SBL polysaccharides (ESBLP), and compared the differences in composition and physicochemical properties between SBL polysaccharides (SBLP) and ESBLP. The antioxidant activity of both SBLP and ESBLP was assessed using DPPH and hydroxyl radical assays in vitro. In addition, their protective effects against AAPH-induced oxidative stress were evaluated in zebrafish embryos. The results indicated that using pectinase with an enzyme dosage of 4500 U/g, at a temperature of 50 °C, a material-to-liquid ratio of 1:1, and a reaction time of 48 h, the polysaccharides content after enzymatic hydrolysis increased from 84.51 to 224.93 mg/g, representing a 179.34% increase. Compared to SBLP, ESBLP exhibited enhanced solubility, oil-holding capacity, and higher L (brightness), a* (redness), and b* (yellowness) values. ESBLP also showed a lower molecular weight and higher protein content. Morphologically, the dense sheet-like structure of SBLP transformed into a fragmented porous surface in ESBLP, with notable changes in monosaccharide composition. In vitro experiments demonstrated that ESBLP had a stronger scavenging ability against DPPH and hydroxyl radicals. In an oxidative stress model using zebrafish, ESBLP significantly reduced the production of reactive oxygen species (ROS) and lipid peroxidation levels. In conclusion, the ESBLP we prepared not only showed increased polysaccharides content and improved physicochemical properties but also exhibited superior antioxidant activity. These findings provide valuable insights for the further development and utilization of SBL. Graphical Abstract